A concise synthesis of 4-nitrophenyl 2-azido-2-deoxy- and 2-acetamido-2-deoxy-D-mannopyranosides - Popelová, Alena; Kefurt, Karel; Hlavácková, Martina; Moravcová, Jitka (Carbohydrate research, 2005)
4-nitrophenyl 3,4,6-tri-O-acetyl-2-azido-2-deoxy-alpha- and beta-D-mannopyranosides were prepared from methyl 4,6-O-benzylidene-alpha-D-glucopyranoside and 1,3,4,6-tetra-O-acetyl-alpha-D-glucopyranose, respectively. Chemoselective reduction of both azides with hydrogen sulfide readily afforded 4-nitrophenyl 2-acetamido-4,6-di-O-acetyl-2-deoxy-alpha-D- and -beta-D-mannopyranosides in higher yields than reduction with triphenylphosphine or a polymer-supported triarylphosphine. Subsequent de-O-acetylation yielded 4-nitrophenyl 2-acetamido-2-deoxy-alpha-D-mannopyranoside and 4-nitrophenyl 2-acetamido-2-deoxy-beta-D-mannopyranoside in 20% and 44% overall yields, respectively.
Keywords: Mannose; mannosa; Molecular Structure; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; molekulární struktura